2019
DOI: 10.1111/ajt.15500
|View full text |Cite
|
Sign up to set email alerts
|

Access to the waiting list and to kidney transplantation for people living with HIV: A national registry study

Abstract: We compared access to a kidney transplantation (KT) waiting list (WL) and to KT between people living with HIV (PLHIV) and HIV‐uninfected controls. Using the REIN (the national Renal Epidemiology and Information Network registry), we included all PLHIV initiating dialysis in France throughout 2006‐2010 and HIV‐uninfected controls matched for age, sex, year of dialysis initiation, and the existence of a diabetic nephropathy. Patients were prospectively followed until December 2015. We used a competitive risk ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…49 We did not observe this phenomenon, nor has this been reported in other HIV D+/R+ or HIV D−/R+ KT cohorts. 10,21,50,51 Longer term follow-up will be important, particularly in light of a recent HIV D+/R+ KT case report in which the donor's HIV strain was detected in recipient urine and blood posttransplant. 52 Notably, we found that D− recipients had a higher incidence of DGF (42% D− vs 12% D+, P = .01) which was not explained by cold ischemia time or donation after cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 We did not observe this phenomenon, nor has this been reported in other HIV D+/R+ or HIV D−/R+ KT cohorts. 10,21,50,51 Longer term follow-up will be important, particularly in light of a recent HIV D+/R+ KT case report in which the donor's HIV strain was detected in recipient urine and blood posttransplant. 52 Notably, we found that D− recipients had a higher incidence of DGF (42% D− vs 12% D+, P = .01) which was not explained by cold ischemia time or donation after cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-positive (HIV+) individuals have a higher incidence of end-stage renal disease (ESRD) [1][2][3][4] and face nearly 3-fold higher mortality on dialysis compared to their HIV-negative (HIV−) counterparts. 5,6 Deceased donor kidney transplantation (DDKT) provides a substantial survival benefit to HIV+ individuals with ESRD, 7 but a shortage of donors and access to DDKT for HIV+ candidates [8][9][10] remain major challenges. As organ transplantation among HIV+ recipients continues to grow, 11,12 novel donor sources are needed to address this disparity.…”
Section: Introductionmentioning
confidence: 99%
“…Although wait-list mortality was similar to candidates who were HIV2, candidates with HIV were significantly less likely to receive a living donor kidney transplant (aHR, 0.53; 95% CI, 0.44 to 0.64) or a transplant at all (aHR, 0.72; 95% CI, 0.64 to 0.82). Data from Europe confirms this trend: in a report of 255 HIV1 dialysis patients from the Renal Epidemiology and Information Network registry (8), candidates with HIV were 32% less likely to be wait-listed and 25% less likely to be transplanted. Challenges remain even among those who are able to be waitlisted: candidates with HIV are 12% less likely (aHR, 0.88; 95% CI, 0.79 to 0.99) to receive a first position organ offer (9).…”
Section: Wait-list Outcomesmentioning
confidence: 86%
“…A retrospective cohort study from Cohen et al demonstrated that HIV+ candidates had an 12% lower rate (95% CI 0.79‐0.99) of receiving a first organ offer and an 18% lower rate (95% CI 0.68‐0.98) of transplantation after receiving a first offer compared to HIV‐ candidates, 8 though the reasons why these patients were not offered kidneys while they were actively listed were not clear. Unfortunately, this is not a uniquely US‐based phenomenon—a study from France 9 likewise demonstrated that HIV+ patients were 25% less likely to be transplanted. Despite all the obstacles and limitations reviewed above, over the last decade, ESKD patients with HIV have been transplanted more frequently.…”
Section: Hiv and Eskdmentioning
confidence: 99%